A coassembled peptide hydrogel boosts the radiosensitization of cisplatin. Issue 85 (1st October 2020) - Wang, Qian; Hou, Xiaoxue; Gao, Jie; Ren, Chunhua; Guo, Qingxiang; Fan, Huirong; Liu, Jinjian; Zhang, Wenxue; Liu, Jianfeng
Abstract : The use of a novel coassembled peptide hydrogel enhanced the radiosensitization effect of cisplatin by increasing the number of Pt–DNA adducts, arresting the cell cycle, and promoting the inhibition of cyclooxygenase-2. Abstract : We constructed a novel supramolecular hydrogel by carrying out a coassembly of cisplatin and short naproxen-capped peptides. This procedure boosted the radiosensitization effect of cisplatin by increasing the number of Pt–DNA adducts, arresting the cell cycle, and inhibiting cyclooxygenase-2.